(untitled) (NAU Journal of Technology and Vocational Education, 2024)
While university students of technical and vocational education must transit smoothly from school to work, inquiries patterning the students’ career decisions appear relatively understudied; especially concerning demographic possibilities in predicting their career decision self-efficacy (CDSE). This paper explores the students’ CDSE and the implications of their demographics (sex, academic major, and age) on their career decision self-efficacy (self-appraisal, occupational information, goal selection, planning, and problem-solving). Adopting a correlational survey approach, the participants were 451 university students in technical and vocational education from three geopolitical zones in Nigeria. The adopted CDSE scale used for this study showed a good model fit for its construct validity as well as high-reliability coefficients. Mean, standard deviation, bivariate correlation, t-test, and multiple linear regression statistics were applied for data analyses. Findings revealed that the students possessed some level of appreciable CDSE. Findings of multiple regression analysis revealed that academic major (Agricultural, Business, Home Economics, and Technical Education) has a relative association with CDSE. Meanwhile, the results also showed that the demographics have significant joint association with occupational information, goal selection, planning, and problem-solving; but not self-appraisal.